Book of abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg - Austria (University of Salzburg, Interfakultärer Fachbereich Sport- und Bewegungswissenschaft/USI, 2010)
This congress was organized by the Department of Sport Science and Kinesiology and the Christian Doppler Laboratory "Biomechanics in Skiing" of the University of Salzburg. The scientific programme offered a broad and interdisciplinary spectrum of current research work in alpine and nordic skiing and snowboarding. Internationally well known scientists will presented their keynotes, many colleagues from all over the world discussed their scientific findings in oral or poster presentations. This book contains the abstracts of the keynote lectures, the oral presentations and the poster presentations.